Applications of photonics in agriculture sector: A review - Yeong T.J.; Jern K.P.; Yao L.K.; Hannan M.A.; Hoon H.T.G. (MDPI AG, 2023)
agriculture; food safety; image processing; optics; quality control; Raman spectrometry; Agriculture; Food Safety; Image Processing, Computer-Assisted; Optics and Photonics; Quality Control; Spectrum Analysis, Raman